Law Enforcement Against the Criminal Act of Theft With Violence Based on Law Number 1 Of 2023 Concerning The Criminal Code - Jessica Oktari Marbun; Mhd. Azhali Siregar; Aulia Rahman Hakim Hasibuan (Cattleya Darmaya Fortuna, 2026)
Violent theft remains one of the most serious conventional crimes in Indonesia because it not only causes material losses but also threatens public safety and social order. Although Indonesia has enacted Law Number 1 of 2023 concerning the Criminal Code (National Criminal Code) as part of a comprehensive criminal law reform, studies examining the implications of Article 479 concerning violent theft remain limited. Existing research generally focuses on the application of Article 365 of the former Criminal Code without critically analyzing the legal transformation introduced by the National Criminal Code and its implications for law enforcement effectiveness.This study aims to analyze the legal regulation of violent theft under the previous Criminal Code and the National Criminal Code, compare Article 365 of the former Criminal Code with Article 479 of Law Number 1 of 2023, and evaluate the effectiveness of law enforcement in achieving legal certainty. This research employs normative legal research using statutory, conceptual, and case approaches. The legal materials consist of primary, secondary, and tertiary legal materials collected through library research, supported by Decision Number 2615/Pid.B/2018/PN Mdn.The findings indicate that Article 479 of the National Criminal Code maintains the essential elements of violent theft while introducing a more systematic formulation that reflects contemporary criminal law principles emphasizing legal certainty, proportionality, and social protection. However, the effectiveness of law enforcement remains dependent on the quality of legal institutions, the professionalism of law enforcement officers, supporting facilities, and public legal awareness. This study contributes to the development of Indonesian criminal law by providing a comprehensive legal analysis of the transition from the former Criminal Code to the National Criminal Code concerning violent theft and its implications for future law enforcement practices.